2017
DOI: 10.3233/bme-171656
|View full text |Cite
|
Sign up to set email alerts
|

Histological evaluations of apatite-fiber scaffold cultured with mesenchymal stem cells by implantation at rat subcutaneous tissue

Abstract: These findings suggest that AFSs are a conducive microenvironment for bone regeneration and are well tolerated in vivo. The results provide valuable baseline data for the design of implant studies using tissue-engineered bone constructed by RFB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Regarding the efficacy of h BMMSCs, subcutaneous ectopic bone formation models are commonly used by CBT [40,41]. Previous reports have demonstrated that murine or human bone marrow stromal cells seeded on calcium phosphate (CaP) stimulate the bone formation implanted subcutaneously in immune-compromised mice [42].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the efficacy of h BMMSCs, subcutaneous ectopic bone formation models are commonly used by CBT [40,41]. Previous reports have demonstrated that murine or human bone marrow stromal cells seeded on calcium phosphate (CaP) stimulate the bone formation implanted subcutaneously in immune-compromised mice [42].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a significant technical need of the development for preparing satisfactory prosthetic bone in an extracorporeal setting using a three-dimensional culture method [ 9 , 16 , 17 ]. In the present study, we attempted to prepare prosthetic bone extracorporeally by culturing mouse MC3T3-E1 cells (as a substitute for osteoblasts) in a radial-flow bioreactor with porous β-TCP or HA beads, which are clinically used for transplantation [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, bone formation was confirmed in vivo when AFS and pre-osteodifferentiated cells were implanted. 24) Ohgushi et al 25) conducted an experiment to evaluate the bone-forming ability of HAp ceramics cultured with RBMCs by implanting them at rat subcutaneous tissue. As a result, the formation of new bone was confirmed in the ceramics.…”
Section: Biological Evaluations Of Implanted Samplesmentioning
confidence: 99%